Detecting and managing partial shorts in Cochlear implants: A validation of scalp surface potential testing. (1st August 2022) - Eitutis, Susan T.; Tam, Yu Chuen; Roberts, Iwan; Swords, Chloe; Tysome, James R.; Donnelly, Neil P.; Axon, Patrick R.; Bance, Manohar L.
Abstract: Objective: To investigate the value of scalp surface potentials to identify and manage partial short circuits to ground in cochlear implant electrodes. Design: A retrospective review of patients with suspected partial short circuits. Main outcome measure: Electrical output of individual electrodes was measured using scalp surface potentials for patients reporting a change in hearing function. Electrical output was compared to functional performance and impedance measurements to determine if devices with suspected partial short circuits were experiencing a decrease in performance as a result of reduced electrical output. Electrical output was checked in an artificial cochlea for two implants following explant surgery to confirm scalp surface potential results. Results: All patients with suspected partial short circuits ( n  = 49) had reduced electrical output, a drop in impedances to approximately ½ of previously stable measurements or to below 2 kΩ, an atypical electrical field measurement (EFI) and a decline in hearing function. Only devices with an atypical EFI showed reduced electrical output. Results of scalp based surface potentials could be replicated in an artificial cochlea following explantation of the device. All explant reports received to date ( n  = 42) have confirmed partial short circuits, with an additional four devices failing integrity tests. Conclusion: Surface potential measurements can detect partial shorts and had 100% correlation with atypical EFI measurements, which are characteristic of a partial short to ground in this device. Surface potentials can help determine the degree to which the electrode array is affected, particularly when behavioural testing is limited or not possible.